"Like heart valve clinic, it probably saves lives, but… Who has time for that?" The challenge of disseminating multidisciplinary cancer care in the United States. Issue 18 (14th September 2018) - Osarogiagbon, Raymond U.
Abstract : Multidisciplinary care is much advocated, little practiced. Prabhu Das and colleagues report on their comprehensive review of the published literature from the United States on the effects of this model of care delivery and demonstrate the dearth of high‐quality studies of the process and outcome benefits of this structural model of cancer care delivery.